2015
DOI: 10.1002/jso.23935
|View full text |Cite
|
Sign up to set email alerts
|

Single‐incision robotic colectomy (SIRC): Current status and future directions

Abstract: By combining laparo-endoscopic single-site surgery (LESS) techniques with the da Vinci robotic platform, single-incision robotic colectomy (SIRC) aims to further minimize incision-related complications and improve cosmetic outcomes from the current standard of care, laparoscopic colectomy. While there is limited literature on SIRC, all available reports suggest SIRC to be a safe and feasible procedure in terms of perioperative outcomes. Future research should focus on further clarification of proposed benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…There is only one study reporting the learning curve of SIRA which states a cutoff of 21 operations (17). This is comparable to conventional robotic multiport adrenalectomy (20) procedures. In this study, the difference in mean operative time between the first 7 cases and 7 cases after passing threshold was 21 minutes (17).…”
Section: Learning Curvementioning
confidence: 99%
See 2 more Smart Citations
“…There is only one study reporting the learning curve of SIRA which states a cutoff of 21 operations (17). This is comparable to conventional robotic multiport adrenalectomy (20) procedures. In this study, the difference in mean operative time between the first 7 cases and 7 cases after passing threshold was 21 minutes (17).…”
Section: Learning Curvementioning
confidence: 99%
“…Although several authors reported no significant difference in operative time in single incision surgeries, Juo et al (20) found increased rates of surgical site infections and incisional hernia when they compared outcomes of single incision robotic colectomy with laparoscopic colectomy.…”
Section: Rationale For Siramentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, robotic surgery can be combined with both SILS, and also with transanal surgery, as outlined below. 33…”
Section: Robotics and Ibdmentioning
confidence: 99%
“…The system has been used largely in the clinical setting for cholecystectomies 120,121 and hysterec-tomies. 122,123 A few case reports have been published so far describing right colectomy, [124][125][126] and one single case report describes the application of da Vinci in single-incision robotic total colectomy. 127 Finally, a new single-site robotic platform realized by Intuitive Surgical is currently under development.…”
Section: Robotics and Single Access Surgerymentioning
confidence: 99%